Longitudinal changes in blood-based biomarkers in chronic moderate to severe traumatic brain injury: preliminary findings. (23rd February 2021) - Schnakers, Caroline; Divine, James; Johnson, Micah A.; Lutkenhoff, Evan; Monti, Martin M.; Keil, Katrina M.; Guthrie, John; Pouratian, Nader; Patterson, David; Jensen, Gary; Morales, Vanessa C.; Weaver, Kathleen F.; et al.
ABSTRACT: Objectives : This longitudinal study aims at 1) providing preliminary evidence of changes in blood-based biomarkers across time in chronic TBI and 2) relating these changes to outcome measures and cerebral structure and activity. Methods : Eight patients with moderate-to-severe TBI (7 males, 35 ± 7.6 years old, 5 severe TBI, 17.52 ± 3.84 months post-injury) were evaluated at monthly intervals across 6 time-points using: a) Blood-based biomarkers (GFAP, NSE, S100A12, SDBP145, UCH-L1, T-tau, P -tau, P -tau/T-tau ratio); b) Magnetic Resonance Imaging to evaluate changes in brain structure; c) Resting-state electroencephalograms to evaluate changes in brain function; and d) Outcome measures to assess cognition, emotion, and functional recovery (MOCA, RBANS, BDI-II, and DRS). Results : Changes in P -tau levels were found across time [ p = .007]. P -tau was positively related to functional [ p < .001] and cognitive [ p = .006] outcomes, and negatively related to the severity of depression, 6 months later [R = −0.901; p =.006]. P -tau and P -tau/T-tau ratio were also positively correlated to shape change in subcortical areas such as brainstem [T(7) = 4.71, p = .008] and putamen [T(7) = 3.25, p = .012]. Conclusions : Our study provides preliminary findings that suggest a positive relationship between P -tau and the recovery of patients with chronic TBI.